2011
DOI: 10.1093/tropej/fmr080
|View full text |Cite
|
Sign up to set email alerts
|

Developing Nomogram to Estimate Birth Weight from Head Circumference and Mid-Upper Arm Circumference

Abstract: The birthweight estimation nomogram is an inexpensive and convenient tool for use in the community setting where weighing machines may not be always available and may thus allow prompt and early referral.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
4
1
Order By: Relevance
“…For chest circumference, most studies have recommended cut-points ranging from 29.5 cm to 33.5 cm for predicting LBW newborns [ 9 , 19 , 20 , 22 , 29 ], which are similar to the cut-points identified in in our study. For MUAC, several studies selected cut-points ranging between 9.0 cm and 10.0 cm, which were slightly higher than observed in our study [ 8 , 19 21 , 30 ]. Determining the optimal cut-point for identifying small newborns may need to be determined in individual populations as the “optimal” measurements may vary for a variety of reasons including technique, ethnic differences, different measurement tools used to determine GA, and differences in the definition of what constitutes the optimal cut-point.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…For chest circumference, most studies have recommended cut-points ranging from 29.5 cm to 33.5 cm for predicting LBW newborns [ 9 , 19 , 20 , 22 , 29 ], which are similar to the cut-points identified in in our study. For MUAC, several studies selected cut-points ranging between 9.0 cm and 10.0 cm, which were slightly higher than observed in our study [ 8 , 19 21 , 30 ]. Determining the optimal cut-point for identifying small newborns may need to be determined in individual populations as the “optimal” measurements may vary for a variety of reasons including technique, ethnic differences, different measurement tools used to determine GA, and differences in the definition of what constitutes the optimal cut-point.…”
Section: Discussioncontrasting
confidence: 52%
“…A meta-analysis of studies that have assessed anthropometric measures as predictors of LBW found chest circumference to be the best predictor, followed by MUAC [ 8 ]. Similarly, some studies have found that chest circumference had the highest correlation (r = 0.60 to 0.85) with LBW [ 19 21 ], although others have found the correlation with LBW to be highest with MUAC, with estimates ranging from r = 0.66 to 0.95 [ 20 22 ]. Foot length has been shown in a meta-analysis to have the weakest correlation with LBW [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the newborn period, anthropometrics are typically limited to observations of weight, length and head circumference. Yet, a limited body of work suggests other measurements may hold value for estimating GA or low birth weight, identifying nutritional management issues and predicting neurodevelopmental outcomes (Arisoy & Sarman, 1995; Das et al, 2012; Kaur et al, 2015; Marchant et al, 2014; Pfister & Ramel, 2014; Sauerborn et al, 1990; Thawani et al, 2013). Normative data for anthropometric and other measures of body composition will be increasingly important for paediatricians and neonatologists as we expand our knowledge of the association with early weight gain and later development of metabolic syndrome (Ekelund et al, 2007; Koyama et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In view of these constraints, several workers in various countries of the world have attempted to identify various alternative anthropometric measurements that can be used to identify LBW babies soon after delivery. [10][11][12][13][14][15][16][17][18][19] In Nigeria, Ezeaka et al 20 and Olusanya 21 carried out 2 of such studies in the southwestern part, while Achebe et al 22 and Ndu et al 23 conducted similar studies in the southeast. Related studies from here had looked at the birth weights of preterm infants, 24 incidence of LBW, [25][26][27][28] and birth weights of full-term newborn babies.…”
Section: Introductionmentioning
confidence: 99%